Detecting bubbles in the Finnish housing markets 2006-2023 - Vaunumäki, Lauri Viljami (My University, 2023)
The research motivation for this study derives from the importance of understanding housing markets as it has a great effect on people’s lives, their financials and the macroeconomy. Throughout the history, housing markets have also been an important factor in a variety of economic crises. Therefore, a housing bubble detection study contributes a lot in order to analyze the housing markets and detect possible price bubble scenarios. The housing prices from the Finnish capital area and from Finland are collected from the secondary housing price data from the first quarter of 2006 to the second quarter of 2023. OLS regression analysis is then performed with real housing prices as the dependent variable and disposable aggregate income and unemployment rates as independent variables. From the fitted values, it is assessed whether the determined bubble thresholds are exceeded during the sample period. The results from the regression analysis are compared to the results received from the ratio analysis conducted with the price-to-rent ratio and price-to-income ratio using the same data that the regression analysis to again evaluate whether the determined bubble thresholds are exceeded. The results indicate that the hypotheses about a housing market bubble between 2020 and 2022 for the Finnish housing markets and for the Finnish capital area housing markets are somewhat confirmed with small variations in the actual bubble periods between the different research methods. The results from the OLS-regression model, price-to-rent ratio and price-to-income ratio indicate that there is notable bubble activity from 2019 to 2022 depending on the research method.

Syynä tämän tutkimuksen tekemiselle toimii asuntomarkkinoiden ymmärtämisen tärkeys, sillä on suuri vaikutus ihmisten elämään, talouteen ja makrotalouteen. Asuntomarkkinat ovat myös kautta historian olleet tärkeä tekijä erilaisissa talouskriiseissä. Siksi asuntokuplien havaitsemiseen tähtäävä tutkimus auttaa huomattavasti asuntomarkkinoiden analysoinnissa ja mahdollisten hintakuplaskenaarioiden havaitsemisessa. Tätä tutkimusta varten arvot asuntojen hinnoista pääkaupunkiseudulla ja koko maassa kerätään vanhojen asuntojen hintatiedoista vuoden 2006 ensimmäiseltä vuosineljännekseltä vuoden 2023 toiselle neljännekselle. OLS-regressioanalyysi on tehty asuntojen reaalihinnoilla riippuvaisena muuttujana ja tutkimusta varten laskettu arvo alueellisista käytettävistä olevista tuloista sekä työttömyysasteet riippumattomina muuttujina. Sovitetuista arvoista arvioidaan, ylitetäänkö määritetyt asuntokuplan raja-arvot tutkimuksen aikajakson aikana. Regressioanalyysin tuloksia verrataan tuloksiin, jotka on saatu asuntojen hintojen suhteesta vuokratasoon ja asuntojen hintojen suhteesta käytettävissä oleviin tuloihin. Myös näissä suhdeanalyyseissä vertailukohtana on määritetty raja-arvo asuntojen hintakuplalle. Tulokset osoittavat, että hypoteesit asuntomarkkinoiden kuplasta vuosien 2020 ja 2022 välillä Suomen asuntomarkkinoiden ja pääkaupunkiseudun asuntomarkkinoiden osalta vahvistuvat suurelta osin. Ainoastaan pieniä vaihteluita on tarkoissa asuntojen hintakuplien aikajaksoissa eri tutkimusmenetelmien välillä. OLS-regressioanalyysi, asuntojen hinta suhteessa vuokratasoon ja asuntojen hinta suhteessa käytettävissä oleviin tuloihin osittaa raja arvojen ylittyvän tutkimuksen aikajakson loppupuolella vuosien 2019 ja 2022 välillä.
Keywords: housing market; housings; real estate market; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance